First case report of nematode parasitic myelopathy in a wild feline in Brazil - Cláudia Cerutti Dazzi; Alex dos Santos; Tanise Policarpo Machado; Michelli Westphal de Ataíde; Rubens Rodriguez; Ananda Müller Pereira; Paulina Sepúlveda García; Adriana Costa da Motta (Revista Brasileira de Parasitologia Veterinária, 2020)
Abstract Parasitic myelopathy caused by Gurltia paralysans in domestic cats is a disease commonly reported in several South American countries. The adult parasite is lodged in the meningeal veins and spinal cord, often causing clinical manifestations of vascular proliferation, thrombophlebitis, and medullary compression. Wild felines are believed to be the definitive hosts of this parasite. The infection occurs through the ingestion of paratenic hosts, but the life cycle of G. paralysans is not yet clearly understood. In this paper, we discuss a case of parasitic myelopathy in a margay (Leopardus wiedii) that died during post-surgical care. Necropsy revealed focal hemorrhages in the thoracolumbar spinal cord. A microscopic examination revealed adult nematodes and eggs inside the veins of subarachnoid space in spinal cord, suggesting G. paralysans infection. This is first description of parasitic myelopathy in a margay in Brazil.